THE ROLE OF REVERSE MENTORING IN CRYSTALLIZING ADAPTIVE PERFORMANCE (World Bulletin of Management and Law, 2022)
The issue of information privacy and crisis management in recent decades The purpose of this research is to investigate the existence of a relationship between reverse mentoring and adaptive performance, and whether the effect it has is significant or not . The research was conducted in private universities in the central Euphrates provinces in Iraq . The data was collected using the questionnaire tool, which was distributed to (196) individuals from the assistant deans and heads of scientific and administrative departments in private universities in the governorates of the Middle Euphrates . Of the (196) questionnaires that were sent by e-mail or via WhatsApp for each person, (163) were returned for use and analysis, which resulted in a response rate of (83.16%), the target group in the research was the middle administrations of private universities in Middle Euphrates governorates (Warith Al-Anbiya University, Ahl al-Bayt University (PBUH), AlZahra University (PBUH) for Girls, Al-Ameed University, Al-Kafeel University, and the Islamic University) all sample members were targeted . The research conducted data analysis to reveal the relationship between variables using the Pearson correlation factor, as well as the effect of reverse mentoring on adaptive performance using structural equation modeling . The results showed that there is a correlation between reverse mentoring and adaptive performance, as well as reverse mentoring exerts a significant effect on adaptive performance.